2011
DOI: 10.5296/rae.v3i1.601
|View full text |Cite
|
Sign up to set email alerts
|

Aid-Growth Nexus in South Asia: Evidence from Time Series and Panel Cointegration

Abstract: Given the strong likelihood of a sharp decline in remittance flows because of the recent recession, coupled with limited access to the global capital market, foreign aid inflow in South Asia can play an important role in boosting economic growth in this region. In the existing literature, the relationship between foreign aid and per capita real GDP is rather inconclusive. Does aid work in South Asia? We answer this question for five economies in this region: Bangladesh, India, Nepal, Pakistan, and Sri Lanka. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 41 publications
3
8
0
1
Order By: Relevance
“…Furthermore, Njoupognigni and Ndambendia [3] after using dynamic panel analysis found that for 36 sub Saharan African countries foreign aid and FDI have a positive impact to the economic growth. Furthermore, Sakyi [16] supported the results of Das and Choudhary [15], after ARDL test suggested that foreign aid and trade openness have positive impact to the economic growth. On the other hand, Bjerg, et al [17] suggested that without external debt services, foreign aid does not have a direct positive impact to economic growth.…”
Section: Emperical Literaturessupporting
confidence: 69%
See 1 more Smart Citation
“…Furthermore, Njoupognigni and Ndambendia [3] after using dynamic panel analysis found that for 36 sub Saharan African countries foreign aid and FDI have a positive impact to the economic growth. Furthermore, Sakyi [16] supported the results of Das and Choudhary [15], after ARDL test suggested that foreign aid and trade openness have positive impact to the economic growth. On the other hand, Bjerg, et al [17] suggested that without external debt services, foreign aid does not have a direct positive impact to economic growth.…”
Section: Emperical Literaturessupporting
confidence: 69%
“…Das and Choudhary [15] used both time series methods and panel co integration. They have reported that that there is long run positive relationship between foreign aid and per capita income in Nepal, Sri Lanka, Bangladesh and Pakistan.…”
Section: Emperical Literaturesmentioning
confidence: 99%
“…As a result, these studies came up with different results which made aid effectiveness literature inconclusive and mix. Among the several existing studies, some argued for a positive relationship between aid and growth (see Islam, 1992;Snyder, 1993;Gounder, 2001;Moreira, 2005;Chowdhury and Das, 2011;and Kargbo, 2012, among others). Authors in this category were of the opinion that aid increased growth by augmenting savings, financing investments and increasing productivity.…”
Section: Summary Of Past Relevant Empirical Studiesmentioning
confidence: 99%
“…Previously, Burnside and Dollar (2000) showed that aid has a positive effect on growth in developing countries which have good monetary, fiscal and trade policies but in case of poor policies such impact is moderate. Aid-growth linkage was analyzed also in the paper of Chowdhury and Das (2011). Authors' results illustrate that in four from five observed countries there is a positive long run relationship between growth rate of per capita real GDP and aid as a percentage of GDP.…”
Section: Literature Review On Donors' Aidmentioning
confidence: 99%